Amine metabolites in the cerebrospinal fluid of patients with disseminated sclerosis. Issue 6 (June 1974) - Claveria, L. E.; Curzon, G.; Harrison, M. J. G.; Kantamaneni, B. D.
Abstract : Mean homovanillic acid and 5-hydroxyindoleacetic acid concentrations were significantly low in the lumbar CSF of a group of patients with disseminated sclerosis (DS) who were severely disabled but not in the CSF of a less severely restricted group with DS. CSF concentrations were also low in a group of patients with superior cerebellar peduncular tremor due to DS and in a single patient with a similar tremor associated with a post-traumatic brain-stem lesion. The interpretation of abnormal CSF amine metabolite concentrations is discussed in the light of these findings.